B STUDI KOMPREHENSIF FAKTOR PENDORONG MOTIVASI DAN PRESTASI BELAJAR PPKN SISWA KELAS VI MI AL MA’ARIF PLUMPANG TUBAN - nurul ngainin (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Abstrack This study aims to analyze the factors influencing students’ motivation and academic achievement in the Pancasila and Civic Education (PPKn) subject at MI Al Ma’arif Plumpang, Tuban. The research background is based on the low motivation and participation of sixth-grade students in PPKn learning, which affects their academic performance. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that students' motivation and learning achievement are influenced by internal factors such as interest, attitude toward the subject, and students’ physical and psychological conditions. Additionally, external factors also play a crucial role, including the school environment, teaching methods, family support, peer interaction, and classroom atmosphere. Engaging and interactive learning, emotional support from teachers and parents, as well as a conducive learning environment, have been proven to enhance students' enthusiasm and academic performance. This study concludes that improving motivation and achievement in PPKn requires a holistic approach involving the active roles of teachers, parents, and the school environment in a synergistic manner. Keywords: learning motivation, academic achievement, Pancasila Education, internal factors, external factors